2017
DOI: 10.21037/jtd.2017.03.156
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of matrix metalloproteinase 9 in patients undergoing off-pump coronary artery bypass grafting

Abstract: Our study first established a connection between MMP9 and OPCAB procedure, suggesting that MMP9 could be a novel biomarker for identifying perioperative myocardial injury in patients undergoing OPCAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…supporting MMP‑9 as an early stage biomarker of poor outcome in cardiovascular disease potentially reflecting atherosclerotic plaque rupture and myocardial tissue destruction [ 49 ]. The MMP‑9 levels further correlate with left ventricular ejection fraction and were associated with perioperative myocardial injury in coronary bypass grafting [ 48 ], which was an underlying diagnosis in some of our patients. To our knowledge, this is the largest published study to date, demonstrating the prognostic value of MMP‑9 levels in a heterogeneous group of critically ill patients admitted to intensive care.…”
Section: Discussionmentioning
confidence: 99%
“…supporting MMP‑9 as an early stage biomarker of poor outcome in cardiovascular disease potentially reflecting atherosclerotic plaque rupture and myocardial tissue destruction [ 49 ]. The MMP‑9 levels further correlate with left ventricular ejection fraction and were associated with perioperative myocardial injury in coronary bypass grafting [ 48 ], which was an underlying diagnosis in some of our patients. To our knowledge, this is the largest published study to date, demonstrating the prognostic value of MMP‑9 levels in a heterogeneous group of critically ill patients admitted to intensive care.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [13] have reported that serum gelatinase B level may be a significant biomarker [13]. Recent studies, researchers have reported that gelatinase B could be a novel biomarker for CAD [10,12]. Also İn our previous study, serum gelatinase B enzyme levels were higher in patients compared to controls [19].…”
Section: Discussionmentioning
confidence: 57%
“…Gelatinase B (also known as MMP-9 and 92-kDa type IV collagenase), one of the MMP family, is highly expressed in the vulnerable regions of the atherosclerotic plaque. Gelatinase B enzymatically active in atherosclerotic plaques, and are known to be associated with the progression and development of atherosclerotic lesions [9][10][11][12]. Studies have reported that gelatinase B associated with coronary artery disease [10,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatinase B (also known as MMP-9 and 92-kDa type IV collagenase), one of the MMP family, is highly expressed in the vulnerable regions of the atherosclerotic plaque. Gelatinase B enzymatically active in atherosclerotic plaques, and are known to be associated with the progression and development of atherosclerotic lesions [9][10][11][12]. Studies have reported that gelatinase B associated with coronary artery disease [10,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%